Diatomeas perifíticas y algunas características limnológicas de un humedal urbano en la sabana de Bogotá (2011)
Se estudio la composición, diversidad y variaciones espacio-temporales de las diatomeas perifiticas presentes en el humedal Jaboque (Bogotá-Colombia), entre abril de 2009 y enero de 2010. Simultáneamente se evaluaron algunas características físicas y químicas del agua para estimar la influencia de estas variables sobre la diatomoflora. Se encontraron 90 taxones, distribuidos en 28 géneros. Nitzschia, Gomphonema y Pinnularia presentaron la mayor riqueza. Se presentó un patrón espacial donde la parte alta y baja del humedal de condición mesotrófica abundaron especies con sensibilidad a los sólidos, la conductividad y altos niveles de nutrientes como: Achnanthes hungarica (taxón dominante), Gomphonema pseudoaugur, Fragilaria pinnata y Cyclotella meneghiniana, mientras que la zona media con mayor intervención antrópica y de condición eutrófica son dominantes Cyclotella stelligera y Gomphonema parvulum. / Abstract. The composition, diversity, spatial and temporal variation of the periphytic diatoms present in the wetland Jaboque (Bogotá-Colombia), have been studied using samples taken on natural and artificial substrates between April 2009 and January 2010. At the same time had been evaluated some physical and chemical characteristics of the water to estimate the influence of these variables on the diatoms flora. Ninety taxa were found, distributed in 28 genera. Nitzschia, Gomphonema and Pinnularia presented the most richness. In the high and low zone of the wetland Achnanthes hungarica was the specie with greater relative frequency and distribution, while in the middle part characterized for being the area with most anthropic intervention Cyclotella stelligera and Gomphonema parvulum were most abundant. The wetland present seasonal organization, where the high and low zone of the wetland is identify as mesotrophic and dominated species as Achnanthes hungarica, Gomphonema pseudoaugur, Fragilaria pinnata y Cyclotella meneghiniana, which are cosmopolitan and typical mesotrophic waters but with differential tolerance associated mainly with concentrations of nutrients, solids and the conductivity. While that the middle part is eutrophic, characterized for being the area with most anthropic intervention Cyclotella stelligera and Gomphonema parvulum were dominant.